Assessing the Impact of Land Use, Land Cover, and Precipitation on Water Quality in the Funil Stream, Ouro Preto – MG, Brazil (International Journal of Geoscience, Engineering and Technology, 2025)
With population growth, the demand for water resources increases, intensifying environmental pressures. Among these, inadequate land management practices can significantly affect the integrity of aquatic ecosystems. This study investigates the effects of precipitation patterns and anthropogenic changes in the landscape on water conditions in a watershed located in Ouro Preto, Minas Gerais, Brazil. Data on water parameters were collected from the Minas Gerais Water Management Institute (IGAM), precipitation records from the National Institute of Meteorology (INMET), and land cover data from the United States Geological Survey (USGS), analyzed using ArcGIS 10.5/ArcMap®. The results indicate variations in water characteristics associated with increased surface runoff and the mobilization of geological materials, including heavy metals. These changes appear to be linked to soil exposure over time, as observed in remote sensing analyses. Additionally, the presence of mining activities in the area may be a contributing factor to water quality degradation.